2002
DOI: 10.1097/00007632-200209010-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Back Home Trial

Abstract: Study Design. A single-blind randomized controlled trial of a leaflet developed for people with acute low back pain was compared with the usual general practitioner management of back pain.Objective. To test the effectiveness of a patient information leaflet on knowledge, attitude, behavior, and function.Summary of Background Data. Despite the commonality of back pain in general practice, little evidence on the effectiveness of simple interventions such as leaflets and advice on self-management has been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
6
1
Order By: Relevance
“…Previous studies have demonstrated a positive impact of such books for patients [7] or physicians [36] in terms of beliefs about LBP, patients' satisfaction with information [23], [24], patients' knowledge about LBP [25], and number of visits to GPs [37]. However, we failed to demonstrate any effect of the book on disability and pain level in patients reporting persistent pain and, as others, on work absenteeism [29].…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…Previous studies have demonstrated a positive impact of such books for patients [7] or physicians [36] in terms of beliefs about LBP, patients' satisfaction with information [23], [24], patients' knowledge about LBP [25], and number of visits to GPs [37]. However, we failed to demonstrate any effect of the book on disability and pain level in patients reporting persistent pain and, as others, on work absenteeism [29].…”
Section: Discussioncontrasting
confidence: 74%
“…Several guidelines and reviews on the management of acute LBP and cLBP in primary care practice are available [8]–[25]. They mainly concern prescriptions for X-rays and laboratory tests, treatment options, and information about physical and occupational activities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational leaflets enable dissemination of health-related information to many people in a relatively short time. Also, they have been shown to have beneficial effects on knowledge and awareness of different health-related problems, such as arthritis, oral cancer, and diabetes (19)(20)(21), and to affect changes in people's health-related behavior (22,23).…”
Section: Discussionmentioning
confidence: 99%